Pengaruh Kecerdasan Emosional, Kecerdasan Spiritual Terhadap Kinerja Guru Lembaga Pendidikan Yayasan Ibnu Abbas Muna - Karim Darma; Ibnu Hajar; Aidin Hudani Awasinombu; Nuryamin Budi (Pascasarjana Universitas Halu Oleo, 2022)
This study aims to: 1) examine the effect of emotional intelligence on teacher performance, 2) examine the influence of spiritual intelligence on teacher performance, 3) examine the influence of emotional and spiritual intelligence on teacher performance. The object of this research is the Ibn Abbas Muna Foundation Educational Institution. The population of the study was the permanent teachers of the Ibn Abbas Muna Foundation Educational Institution totaling 60 people. The size of the sample determination using the census technique or the population as a sample, thus the research sample amounted to 60 respondents. Collecting data using a questionnaire, the measurement scale using Slovin. The research data were tabulated and analyzed using the SPSS ver 22 software application to determine the results of multiple linear regression analysis. The results showed that: 1) emotional intelligence had a positive and significant effect on teacher performance, 2) spiritual intelligence had a positive and significant effect on teacher performance, 3) emotional intelligence and spiritual intelligence simultaneously had a significant effect on teacher performance.